2019
DOI: 10.15244/pjoes/90635
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Parameters on Photocatalytic Oxidation of Slaughterhouse Wastewater Using TiO2 and Silver-Doped TiO2 Nanoparticles

Abstract: The slaughterhouse industry generates massive amounts of highly polluted wastewater of environmental concern. The discharge of untreated slaughterhouse wastewater (SHWW) into water bodies may cause eutrophication, dissolved oxygen depletion, and change in water temperature, which may pose a threat to aquatic life [1-3]. The leaching/ percolation of SHWW may also lead to the contamination of groundwater resources [4]. Resultantly, people may suffer from diarrhea, typhoid fever, wool sorter diseases, pneumonia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
(48 reference statements)
1
5
0
Order By: Relevance
“…Additionally, it is also suggested that MO molecules decomposed much easier and faster under both alkali and acidic conditions rather than in neutral condition (pH 7), inclining more towards the acidic condition. This analysis agrees with reports made by [22] and [23]. The catalyst surface was negatively charged in alkaline solutions while positively charged in acidic conditions.…”
Section: ) Effect Of Phsupporting
confidence: 92%
“…Additionally, it is also suggested that MO molecules decomposed much easier and faster under both alkali and acidic conditions rather than in neutral condition (pH 7), inclining more towards the acidic condition. This analysis agrees with reports made by [22] and [23]. The catalyst surface was negatively charged in alkaline solutions while positively charged in acidic conditions.…”
Section: ) Effect Of Phsupporting
confidence: 92%
“…In addition, the decreases in COD and TOC were 88% and 78%, respectively. Bukhari et al (2019) investigated the photocatalytic oxidation method for treating effluent from slaughterhouses. According to the scientists, process efficiency rose with an increase in catalyst dosage and reaction duration but declined with a rise in pH.…”
Section: Photochemical/photocatalytic Methodsmentioning
confidence: 99%
“…This process can be enhanced by silver-doped TiO 2 nanoparticles as photocatalyst [42]. Electrons captured by silver react with oxygen more efficiently than those combined with electron hole in TiO 2 .…”
Section: Meat Processing Industrymentioning
confidence: 99%